2023
DOI: 10.1021/acsestwater.3c00083
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Assumptions of Phosphorus-Accumulating Organisms and Glycogen-Accumulating Organisms: Peaceful Coexistence in a Carbon-Limited Sidestream EBPR Demonstration

Abstract: Enhanced biological phosphorus removal (EBPR) is strongly influenced by the influent ratio of readily biodegradable carbon to soluble phosphorus due to the preferences of phosphorus-accumulating organisms (PAO). The sidestream EBPR (S2EBPR) process redirects a portion of return activated sludge (RAS) to a sidestream fermenter, increasing the availability of biodegradable carbon. In this study, we assessed the performance and microbial community structure of a full-scale S2EBPR demonstration supplemented with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, recent findings have shown that Candidatus Accumulibacter and Candidatus Competibacter can coexist without impacts on overall process performance. 48 The presence of Denitratisoma (1% of total reads in CRWS) also confirms the presence of bacteria involved in denitrification or partial denitrification; these heterotrophic bacteria were previously confirmed to directly convert NO 2 − to N 2 . 49 The occurrence of denitrifying bacteria could be explained by the low DO operation of CRWS and by the possibility of the activated sludge flocs performing simultaneous nitrification and denitrification (SND).…”
Section: Overall Microbial Community Trendsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, recent findings have shown that Candidatus Accumulibacter and Candidatus Competibacter can coexist without impacts on overall process performance. 48 The presence of Denitratisoma (1% of total reads in CRWS) also confirms the presence of bacteria involved in denitrification or partial denitrification; these heterotrophic bacteria were previously confirmed to directly convert NO 2 − to N 2 . 49 The occurrence of denitrifying bacteria could be explained by the low DO operation of CRWS and by the possibility of the activated sludge flocs performing simultaneous nitrification and denitrification (SND).…”
Section: Overall Microbial Community Trendsmentioning
confidence: 53%
“…Candidatus Competibacter (18.7% of total reads in CRWS) is a glycogen-accumulating organism (GAO) and is considered a competitor for carbon during EBPR because it consumes VFAs but does not take up phosphorus. However, recent findings have shown that Candidatus Accumulibacter and Candidatus Competibacter can coexist without impacts on overall process performance . The presence of Denitratisoma (1% of total reads in CRWS) also confirms the presence of bacteria involved in denitrification or partial denitrification; these heterotrophic bacteria were previously confirmed to directly convert NO 2 – to N 2 .…”
Section: Resultsmentioning
confidence: 70%
“…This suggests that the operational conditions of the S2EBPR need enhancement to bolster the competition of PAOs against other competitors, aiming for a more stable and efficient biological P removal. Recently, Farmer et al (2023) reported that the relative abundance of Tetrasphaera and Dechloromonas was as high as Ca. Accumulibacter in their monitoring of the microbial community of a full-scale S2EBPR system (Farmer et al, 2023).…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…Recently, Farmer et al (2023) reported that the relative abundance of Tetrasphaera and Dechloromonas was as high as Ca. Accumulibacter in their monitoring of the microbial community of a full-scale S2EBPR system (Farmer et al, 2023). However, their study was published after our microbial community analysis was concluded.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…10 Unlike a conventional EBPR process, the S2EBPR involves recirculating a portion of RAS to an anaerobic SSR to stimulate the growth and activity of PAO. 11,12 In the literature, the anaerobic SSR is also commonly referred to as a sidestream fermenter or RAS fermenter.…”
Section: Introductionmentioning
confidence: 99%